2014
DOI: 10.1039/c4md00070f
|View full text |Cite
|
Sign up to set email alerts
|

Novel phthalimide derivatives with TNF-α and IL-1β expression inhibitory and apoptotic inducing properties

Abstract: 24 compounds were synthesized and their immunomodulation of TNF-α and IL-1β was evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…Copyright@ G SilvaJunior Jose [11,29]. Another study using cyclic imides designed to have selective anti-inflammatory action against cyclooxygenase 2 [COX-2] was performed with 30 imidic compounds.…”
Section: Am J Biomed Sci and Resmentioning
confidence: 99%
“…Copyright@ G SilvaJunior Jose [11,29]. Another study using cyclic imides designed to have selective anti-inflammatory action against cyclooxygenase 2 [COX-2] was performed with 30 imidic compounds.…”
Section: Am J Biomed Sci and Resmentioning
confidence: 99%
“…In 2012, Basaric et al found that phthalimides can produce tumor necrosis factor (TNFα) to suppress tumor cell proliferation [ 9 ]. Furthermore, phthalimide polymers are widely used in biomedical and biological fields with a variety of properties including antimalarial, anti-influenza, anticancer, anti-inflammatory, and antifungal activities, apoptotic-inducing properties, and in applications such as protein sensors, n-type organic semiconductors, and electroluminescence [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The phthalimide (Pht) scaffold has attracted great interest as the basis for the synthesis of various alkaloids and other biologically important pharmacophores [25][26][27][28][29]. Phts are lipophilic and neutral molecules that can easily cross biological membranes, and possess anti-microbial [30] and anti-inflammatory [31] activities.…”
Section: Introductionmentioning
confidence: 99%